A non-pathogenic vibrio for the routine quality control of TCBS cholera medium. Issue 2 (February 1981) - Taylor, J A; Barrow, G I
Abstract : A non-pathogenic "indicator" organism to relapse Vibrio cholerae in the routine quality control of TCBS medium was sought among a large collection of freeze-dried vibrios isolated mostly from environmental sources. One strain, which was consistently more sensitive to inhibition of growth on TCBS medium that strains of V. cholerae and V. parahaemolyticus, is recommended for this purpose. It has been deposited with, and is available from, the National Collection of Type Cultures as NCTC 11218.